DESIGNING A SMALL CORPORATE BUILDING WITH FOUR WORKING COMPUTER DEPARTMENTS USING STATIC ROUTING AND SUBNETTING: DESIGNING A SMALL CORPORATE BUILDING WITH FOUR WORKING COMPUTER DEPARTMENTS USING STATIC ROUTING AND SUBNETTING - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a small corporate building with four working computer departments using static routing is designed and made. Static routes are the most important step in the construction of any computer network. Subnetting is one of the best network tools with that each system and network administrator is able to divide one specific computer network into many subnetworks. Thereby, some network administrators, security professionals and network architects can use the free of charge software program Cisco Packet Tracer in order to design and administer different corporate computer networks.